2011
DOI: 10.1177/0954407011424547
|View full text |Cite
|
Sign up to set email alerts
|

Development of a high-speed two-colour system and its application to in-cylinder diesel combustion temperature and soot measurements with split injections

Abstract: In the present study, a high-speed two-colour system was developed in order simultaneously to investigate the temporal and spatially resolved flame temperature and soot concentration (the KL factor) in the combustion chamber of a diesel engine during the same engine cycle. The new two-colour system features a high-speed video camera and a high-repetition image intensifier. It is capable of capturing images at a high sampling frequency, so as to allow the possibility of investigating the flame temperature and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Fouling of the optical window may also influence the measured temperature and KL factor [35]. The impact is greater on KL than on temperature, as the KL factor is proportional to the radiative intensity while the temperature depends on the ratio of radiative intensities at two wavelengths [13]. For the two-colour pyrometry data reported here, the transmissivity of the optical window before and after each set of measurements was not measured.…”
Section: Sources Of Uncertaintymentioning
confidence: 99%
See 1 more Smart Citation
“…Fouling of the optical window may also influence the measured temperature and KL factor [35]. The impact is greater on KL than on temperature, as the KL factor is proportional to the radiative intensity while the temperature depends on the ratio of radiative intensities at two wavelengths [13]. For the two-colour pyrometry data reported here, the transmissivity of the optical window before and after each set of measurements was not measured.…”
Section: Sources Of Uncertaintymentioning
confidence: 99%
“…The measurement of flame temperature in low temperature diesel combustion engines is not widely reported with only a few studies known to the authors [11,12,13,14] with reported temperatures using two-colour pyrometry down to 1650 K. Most of the optical studies have been conducted on purpose built optical engines, where a Bowditch extended piston is combined with an optical window in the piston bowl to provide spatially resolved images. Such a nonrepresentative piston bowl will significantly impact the interaction between the diesel spray and the piston.…”
Section: Introductionmentioning
confidence: 99%
“…Soot, once present within a flame, plays an important role in radiative heat transfer: 3,4 soot produces broadband incandescent radiation, which typically dominates over narrow-band radiation from intermolecular processes. Laser diagnostics measurements conducted in high-temperature, high-pressure combustion vessels [10][11][12][13][14] are typical tools capable of yielding detailed measurements of soot processes under diesel-like operation conditions. The combustion efficiency then tends to decrease.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on soot formation involved detailed analysis of the effect of alternative fuels [22][23][24][25][26][27], fuel injector nozzle design [28], fuel injection pressure [29,30], injection strategy [35,36], and Exhaust Gas Recirculation (EGR) [37][38][39]. Modifications of engine operating parameters through the application of the aforementioned techniques resulted in significant reduction in soot emission.…”
Section: Introductionmentioning
confidence: 99%